Crop productivity of Central European Permaculture is within the range of organic and conventional agriculture - Reiff, Julius; Jungkunst, Hermann F.; Antes, Nicole; Entling, Martin H. (Peer Community Journal, 2025)

(untitled)
Permaculture is a promising framework to design and manage sustainable food production systems based on mimicking ecosystems. However, there is still a lack of scientific evidence especially on the crop productivity of permaculture systems. In this first study on permaculture yield, we collected yield data of eleven permaculture sites in Germany and surrounding countries, that also work according to organic guidelines. We used the Land Equivalent Ratio (LER) as an index to compare mixed cropping systems of permaculture sites with average monoculture yield data of the overall German agricultural sector, as well as that of only organic German agriculture. An LER of 1 indicates equal yields of the compared polyculture and monoculture, while an LER of 1.2 would indicate a 20% higher productivity of the polyculture. Mean permaculture LER as compared to total German agriculture was 0.80 ± 0.27 and 1.44 ± 0.52 as compared to German organic agriculture, both with no significant difference to 1. Our results imply, that yields of permaculture sites are comparable to predominant industrial agriculture. The observed productivity may result from the application of key permaculture principles, such as utilizing diversity and mutually supportive species and improving soil health, which contribute to system stability and resource efficiency. Provided that future studies will support our findings, permaculture could combine soil, biodiversity and climate protection with agricultural productivity. Most importantly, the variables that determine the difference in crop productivity among permaculture sites need to be identified and evaluated.